Clay Edison : The Lost Coast - Book 5 - Kellerman, Jonathan; Kellerman, Jesse (New York : Ballantine Books, 2024)
"It's been almost a year since Clay Edison was forced out of his job at the coroner's bureau. Now he's on his own, working as a private eye, scraping by. Clay is brought a fraud case that begins with a man surprised to learn that he's been named the executor of his grandmother's estate. Her accounts are a mess, and not everything is adding up. He's at the end of his rope and needs Clay's expertise. As Clay dives deeper into a decades-old scheme targeting the vulnerable, his investigation leads him to a bizarre town buried in the remote California wilderness. The residents don't care much for outsiders. They certainly don't like Clay asking questions. And they'll do just about anything to shut him up"--
Keywords: Thrillers (Fiction); Novels